2011
DOI: 10.1002/cm.20530
|View full text |Cite
|
Sign up to set email alerts
|

Actin‐depolymerizing factor homology domain: A conserved fold performing diverse roles in cytoskeletal dynamics

Abstract: Actin filaments form contractile and protrusive structures that play central roles in many processes such as cell migration, morphogenesis, endocytosis, and cytokinesis. During these processes, the dynamics of the actin filaments are precisely regulated by a large array of actin‐binding proteins. The actin‐depolymerizing factor homology (ADF‐H) domain is a structurally conserved protein motif, which promotes cytoskeletal dynamics by interacting with monomeric and/or filamentous actin, and with the Arp2/3 compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
147
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(163 citation statements)
references
References 229 publications
(323 reference statements)
3
147
0
4
Order By: Relevance
“…Thus, human GMF␤ and GMF␥, which share 17.6 and 15.5% sequence identities with human cofilin-1, respectively, display a three-dimensional fold similar to that of other members of the ADF/cofilin family (6). Members of this family, including twinfilin, Abp1, drebrin, and coactosin, are generally implicated in regulation of actin cytoskeleton dynamics (1).…”
Section: Glia Maturation Factor (Gmf)mentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, human GMF␤ and GMF␥, which share 17.6 and 15.5% sequence identities with human cofilin-1, respectively, display a three-dimensional fold similar to that of other members of the ADF/cofilin family (6). Members of this family, including twinfilin, Abp1, drebrin, and coactosin, are generally implicated in regulation of actin cytoskeleton dynamics (1).…”
Section: Glia Maturation Factor (Gmf)mentioning
confidence: 97%
“…2 is a 17-kDa protein conserved from yeast to human (1). Mammals express two GMF isoforms, GMF␤ and GMF␥, which share 82% sequence identity but display different tissue distributions (2).…”
Section: Glia Maturation Factor (Gmf)mentioning
confidence: 99%
See 1 more Smart Citation
“…17 The dynamic assembly and disassembly of filaments and the formation of larger scale filament structures, F-actin out of monomeric G-actin, are crucial aspects of the function of actin and are therefore under scrupulous control by over 100 actinbinding proteins. 47 In this study, we identified multiple cytokine-and GLP-1-responsive proteins such as actin-related protein 3 (ARP3), F-actin-capping protein subunit beta (CAPZB), and heat shock protein beta-1 (HSPB1), which are involved in F-actin polymerization 48,49 as well as proteins such as tropomodulin-3 (TMOD3), which is involved in actin depolymerization. 50 Cytokine-mediated down-regulation of these proteins in human β-cells most likely disrupts the dynamic equilibrium between monomeric G-actin and filamentous F-actin and in this way inhibits GSIS.…”
Section: Journal Of Proteome Researchmentioning
confidence: 99%
“…1, Larbolette et al, 1999;Kessels et al, 2000;Xu and Stamnes, 2006). The ADFH domain is structurally conserved among five families of actin-binding proteins including actin depolymerising factor (ADF)/cofilin, Abp1 and twinfillin (Poukkula et al, 2011). In these other families, the ADFH domain binds globular (G)-or F-actin but there is no evidence of actin binding by the drebrin ADFH domain Chew et al, 2005;Xu and Stamnes, 2006;Grintsevich et al, 2010;Worth et al, 2013).…”
Section: Introductionmentioning
confidence: 99%